PERANCANGAN KINERJA CUSTOMER RELATIONSHIP MANAGEMENT DENGAN MENGGUNAKAN METODE CUSTOMER RELATIONSHIP MANAGEMENT SCORECARD - Nurlailah Badariah; Didien Suhardini; Agung Wahyu Rahmanto (JURNAL TEKNIK INDUSTRI, 2013)
Gading Indah Agency (GIA) is a company that has over than 25 years serving theneeds of print media distribution for its customers. By comparing customer complaint data inJune and December 2010, it is known that an increase in the number of customer complaintsagainst the service company by 0.73% which may indirectly indicate the declining performanceof the company. Therefore GIA requires a performance management that can measure theperformance of the company as a step to determine the position of the company and then usedas feedback for evaluation. Performance measurement in accordance with the GIA CRMScorecard is a method that has the perspective of customer-focused orientation. Stages ofdesigning a model of CRM Scorecard in the company's vision begins with the translationcompany's mission to the CRM Scorecard in four perspectives, namely Customer Value,Customer Satisfaction, Customer Interaction, Customer Knowledge and GIA have 10 strategicobjectives from the perspective of translation CRM Scorecard.